Comparative and chemical proteomic approaches reveal gatifloxacin deregulates enzymes involved in glucose metabolism - Suresh, Kesavan K.; Bhosale, Santosh D.; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J. (Journal of Toxicological Sciences, 2011)
Gatifloxacin has been associated with increased risks of hypoglycemic and hyperglycemic side effects. In order to understand the molecular mechanism of gatifloxacin induced deregulation of glucose metabolism, a Combination of comparative and chemical proteomic approaches were employed using yeast as a model system. Differential protein expression studies using two dimensional electrophoresis and mass spectrometry reveal that gatifloxacin deregulates the expression of key enzymes involved in glucose metabolism. Furthermore, affinity chromatography and LC-MSE analysis led to identification of enolase, as one of the key gatifloxacin binding proteins. Fluorescence spectrometric studies confirmed that the gatifloxacin indeed binds to enolase. Role of enolase in regulation of gatifloxacin induced dysglycemic effect is discussed.
Keywords: antibiotics; Differential protein expression; Fluoroquinolone; Glycolysis; Yeast

Zoom-in - a targeted database search for identification of glycation modifications analyzed by untargeted tandem mass spectrometry - Bhonsle, Hemangi S.; Korwar, Arvind M.; Kesavan, Suresh K.; Bhosale, Santosh D.; Bansode, Sneha B.; Kulkarni, Mahesh J. (European Journal of Mass Spectrometry, 2012)
Post-translational modifications (PTMs) are very important to biological function, however their identification and characterization is technically challenging. In this study, we have identified glycation modifications by nano LC-MSE, a data independent acquisition work flow, followed by database search using the Protein Lynx Global Server (PLGS). PLGS search with a complete human protein database hardly identified glycation modifications in a glycated human serum albumin (HSA), which was detected to be glycated by western blotting with advanced glycation end products (AGE) antibody and fluorescence spectroscopy. To overcome this difficulty, ``Zoom-In'' approach, a targeted database search was used to identify glycation modifications in a glycated HSA, which were further manually validated. This approach was useful for identification of glycation modifications from untargeted tandem mass spectrometry workflow such as MSE, but may require the development of a new algorithm or an upgrade of the existing software.
Keywords: advanced glycation end products (AGEs); data independent acquisition; Diabetes; post-translational modifications

Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.